The Development of Radio Broadcasting Teaching Material to Enhance Students Learning Comprehension - Nini Wahyuni; Mutia El Khairat; Novi Fitria; Titin Ritmi (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2023)
Teaching materials are a set of materials arranged systematically and attractively that allows students to learn. It is designed and written by using instructional principles to support the teaching-learning process. Moreover, it has a significant role in facilitate the educator in carrying out learning and assist students in obtaining alternative teaching material which are sometimes difficult to obtain. Therefore, this study aims to develop teaching material for the Radio Broadcasting course. In addition, the materials were made to achieve the expected goals and to enhance students’ competencies, especially in Radio Broadcasting. There were several stages in developing the materials such as finding the needs analysis, designing the lesson plan, product development, product validation, and product revision. The data collection was obtained through questionnaires and interviews. Then, the data was analyzed descriptively. Based on the needs analysis data, it showed that 62,2% of the students believed that getting appropriate printed references in Radio Broadcasting was difficult. Then, 77% of the students require a textbook for the Radio Broadcasting subject. Based on the data, the result of this study was Radio Broadcasting teaching materials in the form of a module. This module was assessed by the radio expert. The average score for the assessments was 3,1 which means good. This module is expected can assist students in obtaining alternative learning materials and improve their comprehension in Radio Broadcasting. Keywords— radio broadcasting, develop, learning material, English Department